Novel interactions of volatile anaesthetics on O2 sensing and TASK channels in carotid body type-1 cells - Huskens, N (2015)
Hypoxia elicits a carotid body-mediated increase in minute ventilation, called the chemoreflex. Volatile anaesthetics depress this chemoreflex, even at sub-anaesthetic doses. The broad aim of this thesis is to explore how these anaesthetics act on carotid body mechanisms to depress the chemoreflex. The agents studied in this thesis are halothane (a potent depressant of this reflex), isoflurane (a less potent depressant) and sevoflurane (a weak depressant). Intracellular Ca2+ measurements, mitochondrial NADH and potential measurements, and single channel electrophysiology studies were performed on a primary culture of rat carotid body type-1 cells and HEK cells transiently expressing TASK channels. Cells were exposed to hypoxia and/or volatile anaesthetics. The results reveal that on all levels studied, the same order of potency of anaesthetics was observed as seen in human ventilatory studies. Volatile anaesthetics depress the hypoxia evoked Ca2+ entry in the carotid body and increase the activity of K+ background channels both in glomus and HEK cells expressing TASK. Furthermore, on all levels studied, when halothane and isoflurane were applied as a mixture, the effect evoked by the mix was of a lesser magnitude than that of the halothane alone, revealing a novel sub-additive observation, which has not been previously reported in the literature. The anaesthetic action of glomus cells was not exclusive to the TASK channels as application of all three anaesthetics evoked an increase in mitochondrial NADH and caused mitochondrial depolarization in glomus cells. These effects of anaesthetics on mitochondria mimics the effects of hypoxia, the implications of which are discussed in this thesis. Two novel TASK blocking agents A1899 and PK-THPP were able to decrease glomus cell TASK channel activity, even in the presence of a clinically relevant concentration of isoflurane. These agents may be promising as future respiratory stimulants.